Functioning and precipitation-displacement modelling of rainfall-induced deep-seated landslides subject to creep deformation - Vallet, A.; Charlier, J. B.; Fabbri, O.; Bertrand, C.; Carry, N.; Mudry, J. (Landslides, 2016)
We propose an approach to study the hydro-mechanical behaviour and evolution of rainfall-induced deep-seated landslides subjected to creep deformation by combining signal processing and modelling. The method is applied to the Séchilienne landslide in the French Alps, where precipitation and displacement have been monitored for 20 years. Wavelet analysis is first applied on precipitation and recharge as inputs and then on displacement time-series decomposed into trend and detrended signals as outputs. Results show that the detrended displacement is better linked to the recharge signal than to the total precipitation signal. The infra-annual detrended displacement is generated by high precipitation events, whereas annual and multi-annual variations are rather linked to recharge variations and thus to groundwater processes. This leads to conceptualise the system into a two-layer aquifer constituted of a perched aquifer (reactive aquifer responsible of high-frequency displacements) and a deep aquifer (inertial aquifer responsible of low-frequency displacements). In a second step, a new lumped model (GLIDE) coupling groundwater and a creep deformation model is applied to simulate displacement on three extensometer stations. The application of the GLIDE model gives good performance, validating most of the preliminary functioning hypotheses. Our results show that groundwater fluctuations can explain the displacement periodic variations as well as the long-term creep exponential trend. In the case of deep-seated landslides, this displacement trend is interpreted as the consequence of the weakening of the rock mechanical properties due to repeated actions of the groundwater pressure.